Feline infectious peritonitis epizootic caused by a recombinant coronavirus - Charalampos Attipa; Amanda S. Warr; Demetris Epaminondas; Marie O’Shea; Andrew J. Hanton; Sarah Fletcher; Alexandra Malbon; Maria Lyraki; Rachael Hammond; Alexandros Hardas; Antria Zanti; Stavroula Loukaidou; et al. (Nature, 2025)
Abstract Cross-species transmission of coronaviruses (CoVs) poses a serious threat to both animal and human health 1–3 . While the large RNA genome of CoVs shows relatively low mutation rates, recombination within genera is frequently observed 4–7 . Companion animals are often overlooked in the transmission cycle of viral diseases; however, the close relationship of feline (FCoV) and canine CoV (CCoV) to human hCoV-229E 5,8 , as well as the susceptibility of these animals to SARS-CoV-2 9 , highlight their importance in potential transmission cycles. While recombination between CCoV and FCoV of a large fragment spanning orf1b to M has been previously described 5,10 , here we report the emergence of a highly pathogenic FCoV–CCoV recombinant responsible for a rapidly spreading outbreak of feline infectious peritonitis (FIP) originating in Cyprus 11 . The minor recombinant region, spanning spike ( S ), shows 96.5% sequence identity to the pantropic canine coronavirus NA/09. Infection has rapidly spread, infecting cats of all ages. Development of FIP appears to be very frequent and sequence identities of samples from cats in different districts of the island are strongly supportive of direct transmission. A near-cat-specific deletion in the domain 0 of S is present in more than 90% of cats with FIP. It is unclear as yet whether this deletion is directly associated with disease development, and it may be linked to a biotype switch 12 . The domain 0 deletion and several amino acid changes in S, particularly the receptor-binding domain, indicate potential changes to receptor binding and cell tropism.